Building a tool to extract markers in embryo development - Villota Miranda, María; Ayensa-Jiménez, Jacobo; Doblaré, Manuel; Heras, J. (Jornada de Jóvenes Investigadores del I3A, 2025)
A Python library is being developed that can automatically extract morphological and morphokinetic markers from time-lapse videos of embryo development. This tool provides objective quantitative information that will serve as the basis for predictive models of embryo viability, improving the embryo selection process in IVF.